To Predict the Occurrence of Esophageal Varices in Chronic Liver Disease Patients Using Transient Elastography (Fibroscan) (Academia Journal of Medicine, 2021)
Background: Chronic liver disease (CLD) is a cause of significant morbidity all over the world including India. Progression of CLD to cirrhosis leads to multiple complications including development of esophageal varices (EV) with its risk of bleeding & consequent morbidity & mortality. Hepatic biopsy with its inherent limitations is still the gold-standard tool for diagnosis of cirrhosis while Upper gastrointestinal Endoscopy (UGIE) with its inherent limitations is still the gold-standard tool for diagnosis of EV in these patients. Transient elastography (TE-Fibroscan) is a recently developed tool for estimating hepatic fibrosis by liver stiffness measurements (LSM) to predict cirrhosis as well as EV in cirrhotic patients. Subjects and Methods: One hundred patients of CLD were enrolled and evaluated by Fibroscan for LSM and by UGIE for EV & their grades following approval from Institutional Ethics Committee and after obtaining the informed consent. Various statistical methods and tools were then used to find out correlation of LSM with grade of EV and bleeder vs non-bleeder EV. Results: Majority of the patients were males with 41-50years being the dominant age-group. HCV followed by NAFLD were the commonest identifiable etiologies in our study group. Patients with small varices outnumbered those with large varices (52 vs 39). The mean LSM value increased significantly from no Varices (14.60 ± 0.88) to Small esophageal varices (15.51 ± 2.76) to Large esophageal varices (23.80±3.17) with positive correlation with variceal grade. Mean LSM value for identification of varices was 15.51±2.76kPa while it was 23.80±3.17 kPa for large varices. The bleeders had significantly higher LSM value compared to the non-bleeders (34.93±10.45kPa vs 18.46±5.59kPa). Significantly positive correlation was found between mean LSM; Total, Direct & Indirect Bilirubin; Alkaline Phosphatase and serum Globulin while negative correlation was noted with serum Albumin. Conclusion: The noninvasive nature of TE (Fibroscan) makes it an attractive tool for screening of CLD patients needing UGIE not only for diagnosis of EV but those with large varices needing management. Thus, TE might play a crucial role in not only diagnosis but also in management of EV varices in patients with CLD obviating unnecessary UGIE.
Keywords: Esophageal varices; Chronic Liver Disease; Transient Elastography; Fibroscan